An Unprecedented Antimony(III) Borate with Strong Linear and Nonlinear Optical Responses. (6th March 2020) - Liu, Youchao; Liu, Xiaomeng; Liu, Shuai; Ding, Qingran; Li, Yanqiang; Li, Lina; Zhao, Sangen; Lin, Zheshuai; Luo, Junhua; Hong, Maochun
Abstract: Antimony(III) borates with a stereochemical active lone pair remained unknown, although the first antimony borate was reported more than twenty years ago. Now, the first antimony(III) borate in a closed system is successfully synthesized, namely SbB3 O6 . Remarkably, SbB3 O6 not only exhibits an exceptional linear optical response, that is, birefringence of Δn=0.290 at the wavelength of 546 nm, which is the largest among borates, but also has a strong nonlinear optical response of 3.5 times larger than the benchmark KH2 PO4, exceeding those of most borates. Theoretical calculations reveal that the coexistence of strong linear and nonlinear optical responses in SbB3 O6 should be attributable to the synergistic effect of π‐conjugated B−O anionic groups and Sb 3+ with stereochemically active lone pair. This work provides a new class of optical bi‐functional materials with potential prospects in integrated optical devices. Abstract : Starke Reaktion ! Ein Antimon(III)‐borat, SbB3 O6, wurde synthetisiert. Es zeigt nicht nur eine lineare optische Reaktion (Δ n =0.290 bei 546 nm) – die stärkste unter den Boraten – sondern auch eine starke nichtlineare optische Reaktion (Frequenzverdopplung (SHG): 3.5‐mal höher als die von KH2 PO4 ), die jene der meisten Borate übertrifft.